Pengaruh Endorphin Massage Terhadap Intensitas Nyeri Punggung Pada Ibu Hamil Trimester III: Systematic Review - Mardliyana, Nova Elok; Agustin, Della; Maya Puspita, Irma (Sinar : Jurnal Kebidanan, 2024)
Objective: Back pain is an uncomfortable feeling that pregnant women often experience during the third trimester. The centre of gravity influences the enlargement of the uterus, which stretches outward. Not only that, weakening of the abdominal muscles, changes in body position, and pressure on the back are also influenced by the centre of gravity in the mother's stomach. As a result, the pregnant woman's back will be pulled backwards, and the pregnant woman will arch her neck. This posture causes the lower back to curve and pulls the back muscles, causing pain. Endorphin massage is a massage that stimulates the body to generate endorphin compounds as pain relievers. The research aims to understand and determine the effect of endorphin massage on the intensity of back pain in third-trimester pregnant women. Methods: The method used in this research is the systematic literature review method using the Google Scholar and Research database. The procedure for collecting articles is from quantitative research journals from the last ten years & has a minimum index of Sinta 5. Articles from research journals are searched using the keywords "Endorphin Massage" AND "Pregnant Women". After the article you are looking for matches, the keyword appears; it is then selected again so that five articles are found. Results: Of the five articles, most of them discussed the impact of complementary therapy, significantly endorphin massage, which can minimise back pain felt by pregnant women, and the results showed that there was an influence of endorphin massage on pregnant women in the third trimester. Conclusion: From this literature review research, it can be concluded that endorphin massage influences reducing the intensity of back pain in third-trimester pregnant women